Vocal cord paralysis during the treatment of mantle cell lymphoma with vincristine - (:unkn) unknown (SPRINGER, 2013)
Case description We present a case of a seventy-eight year-old man who developed vocal cord paralysis without any sign of peripheral neuropathy during the treatment of Mantle Cell Lymphoma. He first presented in 2008 with a few bilateral small inguinal lymph nodes. Inguinal lymph node biopsy demonstrated Mantle Cell Lymphoma. Flow cytometry studies of peripheral blood and bone marrow cells were compatible with Mantle Cell Lymphoma. R-CHOP chemotherapy triweekly (Rituximab; Cyclophosphamide; Adriamycin; Vincristine; and Methylprednisolone) was planned. At the end of the second cycle, the patient complained of hoarseness without any symptoms of dysphagia or odynophagia. Direct flexible laryngoscopy showed bilateral vocal cord paralysis. Vincristine was discontinued and the patient's voice gradually resolved in about 4 months. Conclusion Vincristine may cause peripheral, autonomic and cranial neuropathies. However cranial nerve involvement is quite uncommon.
Keywords: Cranial neuropathy; Mantle cell lymphoma; Neurotoxicity; Vincristine; Vocal cord paralysis; ACUTE LYMPHOBLASTIC-LEUKEMIA; INDUCED NEUROPATHY; NEUROTOXICITY; DRUGS